Management of Neonatal Limb Ischemia Secondary to Peripheral Arterial Lines: A Systematic Review - Slee, Samantha Louise; Ma, Yangmyung (Journal of Pediatric Intensive Care, 2022)
Limb ischemia is a rare complication of peripheral arterial lines, but there is inconsistency with management. We aimed to describe the variation in the management of limb ischemia secondary to a peripheral arterial line and to determine a consensus for management. The systematic review consisted of searching PubMed, Scopus, Ovid MEDLINE, Google Scholar, Cochrane Database of Systematic Reviews, and references of journals using pre-trialed medical subject headings terms and articles. The sources were scrutinized against inclusion and exclusion criteria. Twenty-six articles were included for full-text analysis: seven retrospective reviews and 19 case reports. The most common site of insertion was femoral (30%), followed by radial (25%). Seventy-one percent of the patients were treated medically, 18% surgically, 9% both medically and surgically, and one patient was treated conservatively with debridement and accurate approximation. The majority of interventions were successful in treating limb ischemia, with 91% achieving a good outcome. All patients who received glyceryl trinitrate (GTN) and all surgical interventions, including conservative management, achieved good outcomes. Medical management was successful in 92%, whereas a combined approach of surgical and medical management was successful in 75% of patients. There is wide variation in the management of limb ischemia secondary to peripheral arterial lines. There is apparent success observed with topical 2% GTN and surgical interventions, with thrombolysis and, in case of no improvement, with thrombectomy, across various studies. We recommend that an updated international consensus be reached on the management of neonates with limb ischemia secondary to a peripheral arterial line.
Keywords: Arterial line; Ischemia; Neonatal; Systematic review; Treatment